Scientific research, innovation and economic growth : a possible relationship - Phillips, Bruce D (Bruce Dalton) (Rhodes University, Faculty of Commerce, Department of Economics, 1967)
Resources devoted to science, or rather to "new science" or research and development and related technical activities have undergone a remarkable rate of increase over the past two decades throughout most of the world. This phenomenon has been symptomatic not only of the development of the majority of nations in the 'western world' but also of the Soviet bloc, and furthermore, all the indications are that this expansion of scientific activities will continue throughout the present decade. Intro., p. 1.
Keywords: Research -- Economic aspects; Technological innovations; Research -- South Africa